Combustion of Liquid Fuels in the Presence of CO2 Hydrate Powder; Fire; Vol. 6, iss. 8 - Misyura S. Ya. Sergey Yakovlevich; Morozov V. S. Vladimir Sergeevich; Donskoy I. G. Igor Gennadjevich; Shlegel N. E. Nikita Evgenjevich; Dorokhov V. V. Vadim Valerjevich (2023, 2023)
Title screen